Characterization of a Halotolerant Archaeon Haloferax larsenii HA8 Isolated from Solar Saltern for Halocin Production - Monika Chaudhary (Science Faculty of Chiang Mai University, 2019)
Halocins are a new class of potentially useful antibiotics produced by halophilic bacteria and archaea. Only a limited number of halocins have been described so far. This paper is an attempt to characterize halocin produced by haloarchaeal strain HA8 isolated from a solar saltern in Pachpadra, India. The strain was identified as Haloferax larsenii by sequencing of partial fragments of 16S rDNA amplicon. On the basis of antagonistic activity, the strain HA8 was selected as producer strain against an indicator strain HA3. The correlation between growth curve and halocin production profile indicated that maximum halocin production occurred during transition from exponential to stationary phase. The optimum culture conditions for halocin production were found to be: pH 8; temperature 30-40°C; salt concentration 2.5 M. Halocin production was stimulated by UV irradiation, maximum percent induction was 35% after 90 sec of UV exposure. Halocin HA8 was resistant to trypsin digestion but sensitive to proteinase K and was moderately stable in isopropanol. Moreover, it was inactivated at low salt concentrations but was stable at high salt concentrations and no change in activity was observed after its storage at 4°C. It can be concluded that antimicrobial peptide halocin HA8 showed many useful characteristics which can be exploited in industries.